A HISTOPATHOLOGICAL AUDIT OF BRAIN TUMOR RECEIVED IN 3 YEARS AT A SINGLE TERTIARY CARE HOSPITAL.: J Peop Univ Med Health Sci. 2025:15(2), 140-148. http://doi.org/10.46536/jpumhs/2025/15.02.634 - Prih Bashir1, Noshaba Rahat2, Humera Shahzad3, Asma Jalbani4, Zumrud Momin5, Bhawani Shanker6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
OBJECTIVE: To determine the frequency of various brain tumor subtypes in different age groups and gender. METHODS: This retrospective study was done at Pathology Department of JPMC Karachi. Brain tumor specimens submitted in 10% buffered formalin for histopathological evaluation between October 2019 and September 2022, from patients of any age and gender, were included. Tumors were classified according to the WHO Classification of Central Nervous System (CNS) Tumors. Data regarding tumor type, histologic grade, and distribution across age and gender were recorded and analyzed using Microsoft Excel and SPSS 26 version. RESULTS: There were 40.7% specimens of males and 45.8% of females. Meningiomas and astrocytomas were the most common brain tumors, each comprising 31.7% (57 cases), followed by pituitary adenomas (5.6%), medulloblastomas (5%), schwannomas (4.4%), necrotic tumors (2.8%), oligodendrogliomas (2.2%), and ependymomas (1.1%), with rare tumors like hemangioblastoma, osteoma, and undifferentiated high-grade tumors each accounting for 0.6%. Meningiomas were more common in females, while astrocytomas and pituitary adenomas were higher in males (p=0.06). Additionally, astrocytomas and meningiomas were the most common with mean ages of 34 and 41 years; medulloblastomas were more frequent in younger patients, with a significant age difference in tumor types (p=0.03). CONCLUSION: Brain tumors showed diverse histopathological subtypes, with meningiomas more common in females and astrocytomas in males, occurring across all ages with subtype-specific age and gender patterns.